Agronomic and physiological performance of an indica–japonica rice variety with a high yield and high nitrogen use efficiency. Issue 3 (28th April 2020) - Zhu, Kuanyu; Zhou, Qun; Shen, Yong; Yan, Jiaqian; Xu, Yunji; Wang, Zhiqin; Yang, Jianchang
Abstract: Hybrid rice ( Oryza sativa L.) varieties usually need more N application to produce a higher grain yield and exhibit lower N use efficiency (NUE) than inbreds. However, little information is available about the mechanism underlying an indica – japonica rice variety with high yield and high NUE under low N rates. This study investigated this issue. The indica – japonica hybrid rice variety Yongyou 2640 (Y‐2640) and the japonica inbred rice variety Lianjing 7 (L‐7) were grown in a paddy field at N rates of 0 and 200 kg N ha −1 . The results showed that the grain yield and internal NUE (grain yield/total N uptake of plants) of Y‐2640 were 16–23% and 9–10%, respectively, higher than those of L‐7. A higher grain yield for Y‐2640 was mainly attributed to the greater spikelet number per unit area that resulted from greater root oxidation activity at panicle initiation and its higher crop growth rate and net assimilation rate before heading. A higher leaf area index and greater root length, root, and shoot biomass were the important agronomic traits of Y‐2640. Higher cytokinin content and the expression of genes involved in the amino acid transporters OsAAP1 and OsLHT1 in the roots and leaves, a higher photosynthetic NUE, and a greater N harvest index were the main physiological traits of Y‐2640. The results suggest that improved agronomic and physiological performance accounts for the high yield and high NUE for the indica – japonica hybrid rice variety.